2020
DOI: 10.1016/j.nimb.2019.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of radiation defects and modification of micromechanical properties under MgO crystal irradiation with swift 132Xe ions

Abstract: Accumulation of F-type defects under irradiation of MgO crystals by 0.23-GeV 132 Xe ions with fluence varying by three orders of magnitude has been investigated via the spectra of optical absorption and low-temperature cathodoluminescence. The number of single centers continuously increases with fluence without any marks of saturation. At the highest fluence, a mean volume concentration of 3.1 × 10 19 and 3.35 × 10 19 cm −3 is reached for F and F + centers, respectively. The F + emission strongly dominates in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…In order to analyze more precisely the thermal annealing/transformation of different F 2 -type centers, we used the decomposition of RIOA into elementary Gaussian components, each of which serves as a measure of a certain type of radiation defects -a concentration of the corresponding radiation defects can be estimated via the integrated area S or the Gaussian peak intensity (OD at I max ). Recently, the similar decomposition procedure was successfully used for the investigation of the processes of accumulation and subsequent thermal annealing of different single F -type defects in MgO single crystals exposed to irradiation with swift Xeions [ 26,27 ]. Note that the result important from methodological point of view was obtained for MgO in Refs.…”
Section: Resultsmentioning
confidence: 99%
“…In order to analyze more precisely the thermal annealing/transformation of different F 2 -type centers, we used the decomposition of RIOA into elementary Gaussian components, each of which serves as a measure of a certain type of radiation defects -a concentration of the corresponding radiation defects can be estimated via the integrated area S or the Gaussian peak intensity (OD at I max ). Recently, the similar decomposition procedure was successfully used for the investigation of the processes of accumulation and subsequent thermal annealing of different single F -type defects in MgO single crystals exposed to irradiation with swift Xeions [ 26,27 ]. Note that the result important from methodological point of view was obtained for MgO in Refs.…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of various color centers was most comprehensively studied in the alkali halides and some simple oxides. In particular, clear effects of temperature, crystal structure, impurities and the type of radiation [34,35,36,37,38,39,40,41] were reported. Moreover, it has been more than once demonstrated that the saturation effects are most easily observed in case of ion irradiation.…”
Section: Theory and Main Resultsmentioning
confidence: 99%
“…Other Gaussians were connected with the presence of impurities (our samples contain traces of chromium and iron ions) and other as‐grown/radiation defects, and just the origin of some of them (especially, peaked at 5.6 and 6.53 eV) will be considered in the present study. According to our recent studies of radiation damage in MgO [ 22 ] and MgAl 2 O 4 , [ 23 ] the estimation of defect concentration based on both peak intensity and integral of the elementary Gaussian gave identical results. Moreover, it is worth noting from the methodological point of view that even the OD value measured at the location of the Gaussian maximum (if it was earlier determined/known), rather accurately, reflected the concentration of relevant defects being dominant in the RIOA region covered.…”
Section: Methodsmentioning
confidence: 91%